The Relationship Between the Intestinal Parasitic Infections with Leptin Concentration and Some Biochemical Parameters in Babylon Province/Iraq - Nebras A.J. Hussien (Journal of Global Pharma Technology, 2017)
The current study aimed to determination of the relationship between intestinal parasitic infections with leptin, reactive oxygen species (ROS) and total antioxidants in patients in Babylon province, Iraq from the December 2015 to April 2016. The total exanimated person who visited the hospitals (male and female) are 863 person, 85 (9.8%) persons were infected with intestinal parasites (Entamoeba histolytic and Giardia lamblia) included 56 females and 29 males. The patients were divided by age into three groups included 52 ( 1-10 ) years ( 35 females and 17 males ), 19 ( 11-20 ) years ( 13 female 6 males ) and 14 ( 20> ) years ( 8 females and 6 males ). The healthy group included 40 persons which divided to the same groups of patient 20 ( 1-10 ) years ( 10 females and 10 male ), 10 ( 11-20 ) years ( 5 females and 5 males ) and 10 ( 20> ) years (5 females and 5 males ).The results showed significant increase (p<0.05) in serum ROS level in patients infected with parasite infections compare to healthy group, and significant elevated (p<0.05) in leptin level in female patients compared to male patients. When compare between age groups, the results obtained significant decrease (p<0.05) in leptin level in patients aged (1-10 &11-20) years and elevated in age group (>20) years compare to healthy group in the same age, also significant elevated in ROS level in patients aged (1-10 & >20) years compare to healthy groups. The results of parasite type showed significant increased (p<0.05) in ROS level in patients infected with E. histolytic compared to patients infected with G. lamblia. The result showed the infected with parasite effected both leptin and ROS levels, but the total antioxidant did not affect parasitic infections.